2018
DOI: 10.1080/15412555.2018.1485637
|View full text |Cite|
|
Sign up to set email alerts
|

Investigating Fractional Exhaled Nitric Oxide in Chronic Obstructive Pulmonary Disease (COPD) and Asthma-COPD Overlap (ACO): A Scoping Review

Abstract: Chronic obstructive pulmonary disease (COPD) is the most common fixed airflow limitation. Individuals may present with the features of both asthma and COPD called asthma-COPD overlap (ACO) with more severity and worse health-related quality of life than COPD or asthma. One of the promising biomarkers that could be used in clinical practice to differentiate ACO from COPD is fractional exhaled nitric oxide (F). The role of Fractional exhaled nitric oxide (F) in COPD/ACO remains unknown. This scoping review aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Fractional exhaled nitric oxide (FeNO), a reliable marker of airway inflammation in asthma, is considered to be a promising diagnostic tool for ACO. 17 , 18 In countries such as Japan, where CT is widely used and FeNO measuring devices are clinically applied in more than 2000 facilities, the preferred ACO diagnostic criteria are those that emphasize objective indicators including CT imaging, DLCO and FeNO as shown in Table 2 . 19 , 20 Due to the differences in medical resources, country-specific adaptations of the global definition may be required.…”
Section: Definition Of Acomentioning
confidence: 99%
“…Fractional exhaled nitric oxide (FeNO), a reliable marker of airway inflammation in asthma, is considered to be a promising diagnostic tool for ACO. 17 , 18 In countries such as Japan, where CT is widely used and FeNO measuring devices are clinically applied in more than 2000 facilities, the preferred ACO diagnostic criteria are those that emphasize objective indicators including CT imaging, DLCO and FeNO as shown in Table 2 . 19 , 20 Due to the differences in medical resources, country-specific adaptations of the global definition may be required.…”
Section: Definition Of Acomentioning
confidence: 99%
“…A high F E NO of more than 50 ppb, measured at an exhalation flow of 50 mL/s (F E NO 50 ) [6,7], can be used to indicate the possible presence of type-2 inflammation in symptomatic asthmatic patients and the likely location of the response to inhaled corticosteroids (ICS) [8]. The clinical use of F E NO in stable COPD patients is unclear as summarised by a recent scoping review [9]. Finding a relevant F E NO cut-off level for determining the use of ICS in COPD is challenging since many studies have not reported on the smoking status, which lowers F E NO levels in both the general population and the asthma and COPD population [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a recent double-blind randomized placebo-controlled trial including 214 undiagnosed subjects who had cough, wheeze or dyspnea showed that FeNO could be used in clinical practice for patients with non-specific respiratory symptoms in order to predict the ICS response [ 80 ]. Although these studies showed promise for the general use of FeNO in the clinical setting of COPD, it is still unclear whether a FeNO cut-off value could be determined to identify an ICS-responsive subset of COPD patients [ 81 ]. This question is of particular importance because the GOLD guideline limited the use of ICS to only the following types of patients: (i) Group D patients with greater than 300 cells/μL of blood eosinophils in initial pharmacological treatment or in follow-up pharmacological management post exacerbations and (ii) patients with more than 100 cells/μL of blood eosinophils when experiencing more than 2 moderate exacerbations per year or at least one severe exacerbation requiring hospitalization in the prior year [ 11 ].…”
Section: Resultsmentioning
confidence: 99%